Multi-needle capacitance probe for non-conductive two-phase flows - Monrós-Andreu, G.; Martinez-Cuenca, R.; Torró, S.; Escrig, J.; Hewakandamby, B.; Chiva, S. (IOP Publishing, 2016)
Despite its variable degree of application, intrusive instrumentation is the most accurate way to obtain local information in a two-phase flow system, especially local interfacial velocity and local interfacial area parameters. In this way, multi-needle probes, based on conductivity or optical principles, have been extensively used in the past few decades by many researchers in two-phase flow investigations. Moreover, the signal processing methods used to obtain the time-averaged two-phase flow parameters in this type of sensor have been thoroughly discussed and validated by many experiments. The objective of the present study is to develop a miniaturized multi-needle probe, based on capacitance measurements applicable to a wide range of non-conductive two-phase flows and, thus, to extend the applicability of multi-needle sensor whilst also maintaining a signal processing methodology provided in the literature for conductivity probes. Results from the experiments performed assess the applicability of the proposed sensor measurement principle and signal processing method for the bubbly flow regime. These results also provide an insight into the sensor application for more complex two-phase flow regimes.